Illuminating Smiles and Frowns: Visual-Affective Cueing Influences Viewer Perceptions of Page Layout Images. Issue 1 (February 2020) - Grygarová, Dominika; Adámek, Petr; Lukavský, Jiří; Kesner, Ladislav
The present research was motivated by the routine digital media practice of producing page layouts as composite images that include several unrelated pictures. We investigated whether or how visually highlighting affective and positional components of pictures in a viewer's field of vision might influence viewer perception and evaluation of the composite image. We examined combinations of visual, spatial, and affective features of cues in composite images to learn whether they affected the viewer's attentional capture of other affective information in the composite image and viewer's affective evaluations. The manipulation check of the feature combinations (positive/negative affect, presence/absence of highlighted color, central/peripheral position) showed significant effects of these features and their interactions on viewers' eye movements. On the other hand, we observed only a small effect on viewers' affective evaluations. Our results suggested that media page layout designers might manipulate the viewer's attention by visual and positional adjustments of affective components in composite images. Future researchers might use this study's design to better understand the human perception of real media images.